Relationship between fatness, physical fitness, and academic performance in normal weight and overweight schoolchild handball players in Qatar State - Souhail Hermassi (6919487) (2021)
The aim of this study was to examine the correlation between physiological parameters (namely fatness and physical fitness) with academic performance (namely mathematics and science grade point average [GPA]) in normal weight and overweight schoolchild handball players. Thirty-six young male team handball players (age: 9±1 years; body mass: 45.5±14.2 kg; height: 1.38±9.1 m; body fat: 19.7±5.6%) at the highest national league for their age group participated. Anthropometry was examined by measuring body mass, body fat percentage (% BF), and body mass index (BMI). Fitness testing included the Yo-Yo Intermittent Recovery Test (level 1), squat jumps (SJ) and counter-movement jumps (CMJ), and upper-limb throwing performance (2 kg medicine ball seated front throw), a 15 m sprint test, and a T-half test for change-of-direction (COD) ability. Academic performance was evaluated through school records of grade point average (GPA) of mathematics and science. BMI was negatively correlated with science GPA (r = -0.57, p<0.001) and mathematics GPA (r = -0.39, p<0.001). Significant correlations between Yo-Yo test performance and science GPA (r = 0.73, p<0.001) and mathematics GPA (r = 0.66, p<0.001) existed. T-half test score (less time taken meant a superior performance) was negatively correlated with science GPA (r = 0.48, p = 0.003) and mathematics GPA (r = 0.63, p<0.01). In conclusion, fatness and physical fitness (except for the upper-muscular strength) were significantly related to academic performance in in schoolchild handball players. Based on results of this study, it seems pragmatic and appropriate to engage young schoolchild in physical activity as it associates with superior academic performance. Other Information Published in: PLOS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1371/journal.pone.0246476